Lactobacillus rhamnosus Encapsulated in Alginate/Chitosan Microgels Manipulates the Gut Microbiome to Ameliorate Salt-Induced Hepatorenal Injury - Zhang, Zheng; Liu, Jiajian; Li, Mengjie; Yang, Binbin; Liu, Wei; Chu, Zhuangzhuang; Cui, Bo; Chen, Xiao (Frontiers in Nutrition, 2022)
As the essential regulator of intestinal bacterial diversity, probiotics are a potential treatment for chronic high-salt diet (HSD) –induced metabolic dysfunction. Probiotic cells entrapped in microgels have been confirmed as being more effective than free cells in protecting bacteria against unfavorable conditions, that is, enhancing their stress resistance. This study explored the physiological mechanism by which probiotic microgels relieve HSD–induced hepatorenal injury. Herein, Lactobacillus rhamnosus was encapsulated in alginate-chitosan microgels which the percentage of alginate/chitosan was applied 1.5:0.5 (w/w) in this system, and the encapsulation significantly improved the probiotic viability in simulated gastrointestinal conditions. Mice were fed an HSD with L. rhamnosus (SDL) or L. rhamnosus microgels (SDEL). After eight weeks of administration, dietary sodium was confirmed as inducing the hepatic and renal damages in mice, based on indicators, including serum biomarker levels, histopathological features of tissues, and pro-inflammatory cytokine contents in blood levels. However, the serum levels of urea nitrogen, creatinine, uric acid, glutamic-pyruvic transaminase, glutamic-oxalacetic transaminase, and alkaline phosphatase in the SDL and SDEL-fed mice were significantly lowered compared to the HSD-fed mice, especially in the SDEL group. HSD increased the abundances of Anaeroplasma, Enterorhabdus, Parvibacter, and Bacteroides, while the microgels increased the abundances of Lactobacillus, Bifidobacterium, Mucispirillum, and Faecalibaculum. Significant variations of fecal metabolome were validated for SDEL-treated mice, containing those linked to entero-hepatic circulation (e.g., cholic acid), carbohydrate metabolism (i.e., L-lactic acid), and increased antioxidants including citric acid. Furthermore, the probiotic microgels ameliorated intestinal damage by improving barrier and absorption functions. These results augmented existing knowledge on probiotic application for salt toxicity.